2006
DOI: 10.1142/s0192415x06003904
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Levels of Serum Insulin, C-Peptide and Glucose after Electroacupuncture and Diet Therapy in Obese Women

Abstract: Our purpose was to investigate the effects of electroacupuncture (EA) therapy on body weight and on levels of serum insulin, c-peptide and glucose in obese women. 52 healthy women were included in this study and were allocated into three groups: 1) Placebo EA group (n = 15; mean age = 41.8 +/- 4.6 and mean body mass index {BMI} = 33.2 +/- 3.5); 2) EA group (n = 20; mean age = 42.1 +/- 4.4 and BMI = 35.9 +/- 3.6) and 3) Diet restriction group (n = 20; mean age = 42.9 +/- 4.3 and BMI = 34.7 +/- 2.7). EA was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 16 publications
4
44
0
Order By: Relevance
“…Studies of the effect of acupuncture on insulin levels have mixed results, showing in different studies an increase 30 and a decrease 31 after treatment. Obesity, diabetes and insulin resistance are closely related.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the effect of acupuncture on insulin levels have mixed results, showing in different studies an increase 30 and a decrease 31 after treatment. Obesity, diabetes and insulin resistance are closely related.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, acupuncture has been reported to have beneficial effects on glucose metabolism and insulin signalling in obese women. 13 Many studies have shown that circadian misalignment increases insulin resistance and decreases pancreatic function. 14 We have found in previous research that high testosterone levels, similar to those observed in women with polycystic ovarian syndrome (PCOS), have been shown in female rats after 16 weeks of continuous light exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Many mechanisms have been proposed to explain how acupuncture results in weight loss [3,[13][14][15][16][17][18][19][20]. For this indication, multiple needle locations and application procedures are utilized, though most needles are placed along the stomach and spleen meridians and in hunger points on the ear.…”
Section: Discussionmentioning
confidence: 99%
“…For this indication, multiple needle locations and application procedures are utilized, though most needles are placed along the stomach and spleen meridians and in hunger points on the ear. The goal of acupuncture treatments for weight loss is to stimulate satiety and to regulate gastrointestinal functions such as acidic flow, gastrointestinal motility, and metabolism [ Acupuncture also facilitates the patient's ability to adapt to a dietary program and ensures greater weight loss when compared to diet-only weight loss programs [13][14][15][16][17]. By balancing energy distribution via needle insertion into the governing vessel-20, Shenmen points, and points with a psychological effect such as Liv 3 and antidepression points, cerebral cortical functions may be affected, leading to an increase in awareness and adaptation to treatment [17,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation